Research on Influencing Factors of Public in Marine Plastic Waste Management - ZHAO Ling; CHENG Jingtao (Haiyang Kaifa yu guanli)
With the deterioration of the marine environment today, in order to promote the management of marine plastic waste, relevant influencing factors are explored to better enhance public participation in the management of marine plastic waste. Using the fuzzy set qualitative comparative analysis method (fsQCA), this study explores the influencing factors of public participation in marine plastic waste management in Shanghai. The results indicate that: (1) In the configuration of factors influencing participation in governance, environmental cognition, policy identification, participation awareness, and participation pathways all appear as core conditions. (2) Environmental cognition and participation consciousness appear as core conditions in both configurations, playing a major role; Economic level, policy identification, environmental behavior, and participation pathways play an auxiliary role in influencing governance factors. (3) Based on the controllability of conditional variables, strengthening public awareness of the marine environment and increasing public participation awareness are effective ways to enhance the influencing factors of marine plastic waste management. The combined effect of multiple factors reveals the complexity of factors influencing public participation in governance. Strengthening public environmental awareness and participation awareness is an effective choice to enhance public participation in governance.